2019
DOI: 10.1002/ps.5388
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal activity of cardiac glycosides isolated from Adenium obesum

Abstract: BACKGROUND Terrestrial mollusks are one of most important agricultural pests worldwide. Natural phytochemicals have an extended history as a source of pesticides. This study was planned to isolate molluscicidal active compounds from the stems of Adenium obesum. RESULTS The benzene‐soluble fraction of the hydroethanolic extract displayed the most potent molluscicidal activity against Monacha obstructa among different solvent fractions with a median lethal dose (LD50) of 4.91 µg g−1 body weight (bw). The bioacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The two molluscicidal active cardiac glycosides, cerberin 169 and neriifolin 170 (Table 1 ), were isolated from the stems of Adenium obesum (Alzabib et al 2019 ). Products 169 and 170 had significant molluscicidal activity against Monacha obstructa snails with LC 50 values of 5.39 and 4.30 ppm in 24 h, respectively.…”
Section: Development Of Plant Molluscicidesmentioning
confidence: 99%
“…The two molluscicidal active cardiac glycosides, cerberin 169 and neriifolin 170 (Table 1 ), were isolated from the stems of Adenium obesum (Alzabib et al 2019 ). Products 169 and 170 had significant molluscicidal activity against Monacha obstructa snails with LC 50 values of 5.39 and 4.30 ppm in 24 h, respectively.…”
Section: Development Of Plant Molluscicidesmentioning
confidence: 99%
“…Insecticidal effects of glycosides have been reported by several researchers [63][64][65][66][67][68][69].…”
Section: Glycosidesmentioning
confidence: 99%
“…[11][12][13] Thus, the scientific community recommends the search for new molluscicide candidates, of natural or synthetic origin, which are biosafe, stable, have selective action, considered cost-effective in production and application, and that have action against snails in embryonic and adult stages. [14][15][16] Among several natural secondary metabolites produced by plants used in traditional medicine and pharmaceutical industries, naphthoquinones, a class of naphthalene derivatives, have a broad pharmacological and biological spectrum. 17,18 Studies have reported the action of naphthoquinones against immature stages and adults of S. mansoni and S. haematobium, and toxicity against embryos and adults of the species B. alexandrina, B. glabrata and Bulinus truncatus, vectors of medical importance.…”
Section: Introductionmentioning
confidence: 99%